2018
DOI: 10.1590/1678-992x-2016-0320
|View full text |Cite
|
Sign up to set email alerts
|

Sod production and the effects of liquid organo-mineral fertilizers and thickness of sod

Abstract: ABSTRACT:Nitrogen fertilization and an appropriate cutting thickness can result in firmer sod that can be handled in less time with greater turfgrass regrowth during the subsequent cycle.This experiment was conducted on a sod production farm located in Capela do Alto, in the state of Sao Paulo, Brazil. The soil was a dystrophic Rhodic Hapludox (Oxisol) with a medium texture.The experiment had two statistical designs; the initial design was randomized blocks with seven treatments and four replicates. Treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Considering the angular coefficient of the generated equations, each 1% of the applied irrigation depth would provide increases of 1.2, 1.9, 1.2 in RCC at 125, 145 and 190 DAS, respectively (Table 7). Increasing RCC values in response to application of N-containing products was also observed by Gazola et al (2016), Lima et al (2018) and Mota et al (2019). Lima et al (2012) indicated, for bermudagrass cv.…”
Section: Relative Chlorophyll Content (Rcc)mentioning
confidence: 67%
See 1 more Smart Citation
“…Considering the angular coefficient of the generated equations, each 1% of the applied irrigation depth would provide increases of 1.2, 1.9, 1.2 in RCC at 125, 145 and 190 DAS, respectively (Table 7). Increasing RCC values in response to application of N-containing products was also observed by Gazola et al (2016), Lima et al (2018) and Mota et al (2019). Lima et al (2012) indicated, for bermudagrass cv.…”
Section: Relative Chlorophyll Content (Rcc)mentioning
confidence: 67%
“…The lawn was taller in the plots irrigated with DW, both by drip irrigation and sprinkling, when compared with the grass irrigated with TW. This greater plant growth can be attributed to the presence of ions, mainly N, found in larger amounts in DW (average 56 mg L -1 ), as N is considered the main nutrient responsible for shoot growth, in lawns (Gazola et al, 2016, Lima et al, 2018, Mota et al, 2019.…”
Section: Source Of Variationmentioning
confidence: 99%
“…The nutrients in chicken manure, such as nitrogen, phosphorus, and potassium contributed to the improved coverage of the sod by providing the necessary resources for seed germination and growth allowing for quick spread of vegetative parts of the sod. Similarly, Lima et al [23] found that the application of nitrogen fertilizer increased the percentage of ground cover of Zoysia grass, and the application of 400 kg ha−1 N provided the fastest turfgrass closure. Based on the results all the treatments produced a coverage quality value above 55% which is acceptable for commercial turf production according to NTEP protocols.…”
Section: Coveragementioning
confidence: 89%
“…Esmeralda (Zoysia japonica Steud. ), a stoloniferous and rhizomatous species, is the most used species in Brazilian (Lima et al, 2018). The plug size was standardized around 10 cm (Figure 1) including the rhizomes or stolons and the aerial part.…”
Section: Methodsmentioning
confidence: 99%